Edukasi Pencegahan Stroke Berbasis Audiovisual dalam Meningkatkan Health Literacy pada Kelompok Risiko Stroke - Artiawati, Eva; Puspasari, Susy; Herdiman; Kusuma Putri, Tri Antika Rizki (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Introduction: The success of efforts to prevent stroke risk can be achieved by providing information by exposure to information that can increase health literacy. Providing audiovisual-based education is expected to be able to convey information related to stroke risk prevention effectively. Objective: The purpose of this public service was to improve health literacy among stroke risk groups through stroke prevention audiovisual-based education. Method: This public service was conducted by giving audiovisual material about stroke prevention to stroke-risk groups of people. Result: All participants were given the education fully. Health literacy shows improvement after being given the education. Conclusion: The results of this community service show that audiovisual education influences increasing health literacy. Educational activities can be carried out by recruiting larger students and conducting education in a more comfortable environment so that the purpose of education can work optimally.